Observations and Theory of Short GRBs at the Dawn of the Gravitational Wave Era - Stratta, Giulia (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The book starts with a review of the established facts on the numerical simulations of binary neutron star mergers and simulations of short GRB jets that highlights the issues that need to be revised and further clarified, as the need to understand how the relativistic outflow was launched, what the initial structure of the outflow is, and how it evolved through its interaction with the binary ejecta. Constraints on a local population of faint short duration GRBs are then provided in light of the GW170817/GRB 170817A event at d~40